Pemanfaatan Google Form Sebagai Media Ujian Online Pada SMKS Prayatna 1 Medan - Bister Purba; Nelly Astuti Hasibuan; Putri Ramadhani (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
SMKS Prayatna 1 Medan is one of the senior high schools located in Medan that provides various educational support facilities for its students. However, along with the spread of Corona Virus Disease 2019 (COVID-19) which makes some countries set policies to impose lockdowns, such as in Indonesia doing Pembatasan Sosial Berskala Besar (PSBB) policies. Local governments decided to implement policies to engage students and began implementing learning methods with online systems. Some schools are not ready for online learning systems, which require learning media such as mobile phones, laptops or computers as experienced by SMKS Prayatna 1 Medan. It also has an impact on teachers are required to be able to design learning media as an innovation by utilizing online media, one of which is when the implementation of the exam. So , online media technology is needed that can accommodate the implementation of school exams at SMKS Prayatna 1 Medan. One application that can be used as a means of learning is Google Form. Google Form is a free feature from Google that can be used for the creation of online exam forms with various problem modes from multiple choices and essays. It is expected that through training in the use of Google Form as an online exam medium is expected to be a solution to overcome the difficulty of carrying out online exams at SMKS Prayatna 1 Medan. through training in utilizing Google Form as an online exam media is expected to be a solution to overcome the difficulty of conducting online exams at SMKS Prayatna 1 Medan